2011
DOI: 10.1007/s00125-011-2120-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of motivational interviewing on glycaemic control and perceived competence of diabetes self-management in patients with type 1 and type 2 diabetes mellitus after attending a group education programme: a randomised controlled trial

Abstract: Aims/hypothesis The aim of this study was to measure the efficacy of motivational interviewing (MI) compared with usual care on changes in glycaemic control and competence of diabetes self-management in patients with diabetes mellitus.Methods Patients were eligible if they had type 1 or 2 diabetes mellitus, were over 18 years of age and had participated in a 4 day group education programme offered at a diabetes clinic at a university hospital in Denmark. Exclusion criteria included pregnancy, severe debilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 40 publications
2
21
0
2
Order By: Relevance
“…The difference in the weight change may be because the participants in the intervention group in West et al () received a group‐based behavioural weight control programme as well as the motivational interview, and this programme might have provided additional benefit for weight loss. In other studies, which differ in working time, there was no difference between groups for VKI (Meybodi et al, ; Rubak, Sandbæk, Lauritzen, Borch‐Johnsen, & Christensen, ), weight, and waist circumference (Rosenbek Minet et al, ). The results of the that studies show that it takes more time for people to make the desired behaviour change at the cognitive level before the effectiveness of the motivational interview than after it (Rubak, Sandback, Lauritzen, & Christensen, ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The difference in the weight change may be because the participants in the intervention group in West et al () received a group‐based behavioural weight control programme as well as the motivational interview, and this programme might have provided additional benefit for weight loss. In other studies, which differ in working time, there was no difference between groups for VKI (Meybodi et al, ; Rubak, Sandbæk, Lauritzen, Borch‐Johnsen, & Christensen, ), weight, and waist circumference (Rosenbek Minet et al, ). The results of the that studies show that it takes more time for people to make the desired behaviour change at the cognitive level before the effectiveness of the motivational interview than after it (Rubak, Sandback, Lauritzen, & Christensen, ).…”
Section: Discussionmentioning
confidence: 84%
“…Studies on conducting motivational interviews with patients with T2DM have shown that these interviews improve HbA1C, weight loss, control of diet, and physical activity (Chapman et al, ; Chen et al, ; Heinrich, Candel, Schaper, & de Veries, ; Miller et al, ; Poursharif et al, ). On the other hand, another study reported that motivational interviews had no superiority compared with regular care (Rosenbek Minet, Wagner, Lonving, Hjelmborg, & Henriksen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a one-year MI programme was evaluated in a Danish diabetes clinic setting including volunteers with type 1 and type 2 diabetes [29]. Although the study did accomplish a rise in health care providers’ MI competences and a high degree of intervention delivery, the study showed no 12- or 24-month effect on PAID or HbA 1c .…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, one study showed a greater improvement in HbA1c in the non‐Motivational Interviewing groups than in the groups receiving Motivational Interviewing . Another study failed to show any benefit of Motivational Interviewing over and above usual care for either T1D or T2D .…”
Section: Introductionmentioning
confidence: 94%